Pencatatan Akuntansi Pada Usaha Tani Padi (Oryza Sativa) - Dian Yustriawan; Muhammad Lesmana Taufik (Jurnal Riset Akuntansi dan Bisnis, 2020)
The research sample was 30 farmers. The sampling technique was purposive sampling. The data analysis used was descriptive statistical analysis and quantitative analysis. The characteristics of the research respondents that have been known are that the average age of the respondents is 53.9 years, farming experience is 36.2 years, education level is 6.7 years or SD, the area of farming land is 1.1 hectares and most of the farm ownership is by rent. land. The results of this research show that 100% of respondents or all respondents have never gained knowledge of accounting. As for the implementation of farmers in recording accounting on the aspect of transaction evidence, 50% do not know and never keep proof of purchase of production facilities, 70% do not know and never keep proof of payment of labor. There are also very many farmers who do not know and have never done accounting records, namely 76.7% and all respondents (100%) do not know and have never made an income statement.